2019
DOI: 10.1038/s12276-019-0205-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of β-site amyloid precursor protein cleaving enzyme 1 and cholinesterases by pterosins via a specific structure−activity relationship with a strong BBB permeability

Abstract: We extracted 15 pterosin derivatives from Pteridium aquilinum that inhibited β-site amyloid precursor protein cleaving enzyme 1 (BACE1) and cholinesterases involved in the pathogenesis of Alzheimer’s disease (AD). (2R)-Pterosin B inhibited BACE1, acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) with an IC50 of 29.6, 16.2 and 48.1 µM, respectively. The Ki values and binding energies (kcal/mol) between pterosins and BACE1, AChE, and BChE corresponded to the respective IC50 values. (2R)-Pterosin B was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 75 publications
3
14
0
Order By: Relevance
“…These two compounds have been used as references in many studies on AChE and BACE-1 inhibition. The results showed that the biological activities of the positive controls in this study are comparative to previously published values [ 34 , 35 , 36 ].…”
Section: Resultssupporting
confidence: 54%
“…These two compounds have been used as references in many studies on AChE and BACE-1 inhibition. The results showed that the biological activities of the positive controls in this study are comparative to previously published values [ 34 , 35 , 36 ].…”
Section: Resultssupporting
confidence: 54%
“…These two compounds have been used as references in many studies on AChE and BACE-1 inhibition. The results show that the biological activities of the positive controls in this study are comparative to the previously published values [ 56 , 57 , 58 ]. On the other hand, the experimental assays also specified that AC12 had a higher activity than galantamine on AChE and all the synthesized chalcones exhibited the higher inhibiting effects than quercetin on BACE-1.…”
Section: Resultssupporting
confidence: 52%
“…The active-site of BChE is composed of 4 subdomains, i.e., a peripheral site, a choline binding pocket, a catalytic site, and an acyl binding pocket [ 54 ], and the acyl binding pocket contains Trp231, Leu286, and Val288, which permit binding and hydrolysis of ligands and substrates bulkier than those of AChE [ 54 ], which is considered to be largely responsible for the different ligand-binding specificities of AChE and BChE [ 55 ]. Jannat et al reported that (2 S ,3 R )-pretosin C is a noncompetitive inhibitor of BChE and that it hydrophobically interacts with Val288, Lue286, and Phe357, and hydrogen bonds with Gly283 and Asn397, and docks at a non-ligand binding site [ 56 ]. It was also observed that hydrogen bond formation was the main driving force behind BChE–coumarin complex formation, whereas hydrophobic and halogen interactions underpinned AChE interactions with N 1-(coumarin-7-yl) derivatives [ 57 ].…”
Section: Discussionmentioning
confidence: 99%